Islam as moderating variable between celebrity endorsement influence on attitude towards advertisements and purchase intention - Moses, Ibrahim Oyewole; Hasan, Hamisah; Ahmad, Abdul Mua'ti @ Zamri; Tamam, Ezhar (Center for Promoting Ideas, 2018)
Celebrity endorsement has become a common advertising strategy adopted by many companies to attain their marketing objectives. Advertisers often select endorsers as a promotional strategy to communicate the attributes of their products or services to their target audience in order to create a positive impression about the brand. Today, celebrities are endorsing various types of women attire particularly the hijab. While they were more popular in the social media yet, we are also seeing the likes of Dato Siti Nurhahiza, Yuna and Neelofa appearing on television programs donning the hijab as endorsers of various brands. Such activities were categorized as product placement and it is an increasingly popular type of advertisements. Celebrity endorser has the advantage of creating positive impression about the brand and hence creates positive attitudes towards the brand due to the likeability and trustworthiness of the endorser. With the current situation where we are seeing intimidation and assault targeting hijab-wearing women across the globe, it becomes important to focus on such study. Therefore, the aim of this research is to examine the impact of using celebrity endorsement in hijab ads on attitudes towards ads and purchase intentions. The study will also be conducted to examine the followings; i) attitude towards ads ii) attitude toward celebrity endorser iii) attitude toward brand iv) relationship between attitude toward brand and attitude toward ad vi) relationship between attitude toward celebrity endorser and purchase intention vii) relationship between religion, celebrity endorser and purchase intention. An experiment will be conducted on a sample of 200 Muslim women. They will be exposed to hijab advertisements and later will be required to answer a set of questionnaires. The Elaboration likelihood model that was developed by Richard E. Petty and John Cacioppo in 1986 will be applied in the study to explain the different ways hijab wearing women process the endorsement of their favourite celebrities in hijab ads, it will be interesting to examine their involvement in their decision-making process to purchase and also the importance of using Islamic cues in the advertisements.